Building messages for the opioid crisis using the extended parallel process model. Issue 1 (1st January 2021) - Bagley, Braden; Beckham, Jessica
Abstract : As those who are tasked with combating the opioid crisis turn to communication campaigns, it is important to better understand best strategies for designing effective campaign messages. As posited by the extended parallel process model, perceptions of threat and efficacy must be high in order for message recipients to adopt recommended actions. The purpose of this study was twofold: Identify what makes people feel threatened by the opioid crisis and identify what people perceive are efficacious solutions to the opioid crisis. In March of 2018, the Office of National Drug Control Policy launched a website soliciting Americans to share opioid addiction stories. These videos were transcribed by the researchers which served as data for this study. Six themes emerged representing perceived threats of the opioid crisis, including addiction, family struggles, overdose death, stigma, financial repercussions, and legal repercussions. Four themes emerged representing perceived efficacy, including social support, information seeking and sharing, programs and tools, and attention to children. The implications of this study are twofold. First, those who are designing campaigns to address the opioid crisis should include these recommendations in order to convince the public to act. Second, this study has theoretical implications for academics studying opioid messages.